Abnormal NHC ruthenium catalysts: mechanistic investigations of their preparation and steric influence on catalytic performance. Issue 18 (3rd August 2022) - Böth, Alexander D.; Sauer, Michael J.; Baratta, Walter; Kühn, Fritz E.
Abstract : Preparation of bis-aNHC Ru catalysts, identification of formation intermediates and application in transfer hydrogenation and Oppenauer-type oxidation, observing an inversion in activity appearing to be dependent on steric hindrance. Abstract : The bis-abnormal N-heterocyclic carbene (aNHC) ruthenium complexes [Ru(OAc)(aNHC-ethyl-PPh2 )2 ]Br 1 and 3 are obtained from Ru(OAc)2 (PPh3 )2 with the ligands 1-(2-diphenylphosphino-ethyl)-3-aryl-imidazolium bromide (aryl = phenyl, di-iso-propylphenyl) L Ph and L Dipp in THF at 60 °C and in the presence of NaOAc via displacement of PPh3 and carbene deprotonation. Mechanistic studies on the formation of the di-iso-propylphenyl derivative 3 reveal the preceding generation of mono-aNHC intermediate isomers 3a and 3b as kinetic and thermodynamic products. Complexes 1 and 3 exhibit exceptionally high activity in the transfer hydrogenation (TH) of acetophenone and Oppenauer-type oxidation of α-tetralol, 1 showing turn-over frequencies (TOF) of up to 550 000 h −1 in the TH of acetophenone and 3 showing TOFs up to 280 000 h −1 in the Oppenauer-type oxidation of α-tetralol. The comparison of the catalytic activity of the phenyl 1, mesityl 2 and di-iso-propylphenyl 3 complexes follows the order 1 > 2 > 3 for TH, likely due to accessibility of the active center, whilst following the inverse 3 > 2 > 1 order in Oppenauer-type oxidation. This inversion appears to be dependent on steric influences. These observations are in line with buried volume calculations based on density functional theory (DFT) optimized structures.